Women’s services in forensic psychiatry - Vogel, Vivienne de (Seminars in forensic psychiatry, 2024)
The specific risks and mental health needs of women in forensic services and the relevance of gender-responsive treatment include gender differences in criminological and psychiatric characteristics; gender-sensitive risk assessment; and gender-sensitive management. Some recommendations are provided for practitioners working with women in forensic services.